2004
DOI: 10.1515/mamm.2004.033
|View full text |Cite
|
Sign up to set email alerts
|

Bats, climate, and air microorganisms in a Romanian cave

Abstract: Monthly surveys of bat dynamics, temperature, and humidity were performed for the duration of one year in a Romanian cave (Măgurici Cave).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Air samples were collected using the Koch sedimentation method ( Borda et al 2004 , Kuzmina et al 2012 ). Three Petri dishes that contained 2 % potato-dextrose agar (PDA, Difco) were exposed to the atmosphere in the cave for 15 min at each sampling site, then sealed with Parafilm and placed in zip-locked plastic bags.…”
Section: Methodsmentioning
confidence: 99%
“…Air samples were collected using the Koch sedimentation method ( Borda et al 2004 , Kuzmina et al 2012 ). Three Petri dishes that contained 2 % potato-dextrose agar (PDA, Difco) were exposed to the atmosphere in the cave for 15 min at each sampling site, then sealed with Parafilm and placed in zip-locked plastic bags.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that cave fungi might originate from the non‐subterranean environment, as all the recorded genera and most of the identified species in caves have been recorded previously from above‐ground environment (Vanderwolf et al, ; Zhang et al, ). For example, microfungi in cave air were found to be related to those in the air outside caves (Borda, Borda, & Tămaş, ; Docampo et al, ; Wang et al, ) or those in rainfall (Docampo et al, ). By comparing the divergence times of suspected obligate troglobitic fungi to cave formation geologic age, Zhang et al () found that the geographic history of caves is too short for fungal speciation.…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that studies into terrain caves will provide insights into the potential microbial composition, diversity, dynamics and relationships, and evolutionary importance of earlier microbial 1 Advances and Challenges in Studying Cave Microbial Diversity life on Earth and life on other planets (Pedersen 2000 ; Storrie-Lombardi and Sattler 2009 ;Storrie-Lombardi et al 2009 ) . Additionally, studies in sul fi dic and ice caves have also helped elucidate a complex microbial community structure in what is seemingly an inhospitable environment to most life forms (Priscu et al 1999 ;Rohwerder et al 2003 ;Borda and Borda 2006 ;Borda et al 2004 ;Chen et al 2009 ;Rusu et al 2011 ) .…”
Section: General Synopsis Of Cave Habitatsmentioning
confidence: 99%